Light‐Driven Reversible Intermolecular Proton Transfer at Single‐Molecule Junctions. Issue 12 (14th February 2019) - Cai, Shuning; Deng, Wenting; Huang, Feifei; Chen, Lijue; Tang, Chun; He, Wenxiang; Long, Shichuan; Li, Ruihao; Tan, Zhibing; Liu, Junyang; Shi, Jia; Liu, Zitong; et al.
Abstract: Photoresponsive molecular systems are essential for molecular optoelectronic devices, but most molecular building blocks are non‐photoresponsive. Employed here is a photoinduced proton transfer (PIPT) strategy to control charge transport through single‐molecule azulene junctions with visible light under ambient conditions, which leads to a reversible and controllable photoresponsive molecular device based on non‐photoresponsive molecules and a photoacid. Also demonstrated is the application of PIPT in two single‐molecule AND gate and OR gate devices with electrical signal as outputs. Abstract : Out of the blue : By using a photoinduced proton‐transfer (PIPT) strategy, a non‐photoresponsive 1, 3‐azulene derivative can be modulated in single‐molecule junctions by blue light, with conductance variation by almost one order of magnitude. This behavior can lead to potential applications in single‐molecule logic gate devices with electrical outputs.